Paradoxical role of matrix metalloproteinases in liver injury and regeneration after sterile acute hepatic failure - Santos, Mônica Morais; Alvarenga, Débora Moreira; Mattos, Matheus Silvério; Lopes, Mateus Eustáquio; Marchesi, Sarah Cozzer; Araújo, Alan Moreira; Nakagaki, Brenda Naemi; David, Bruna Araújo; Souza, Viviane Aparecida De; Carvalho, Érika; Pereira, Rafaela Vaz Sousa; Marques, Pedro Elias; et al. (Cells, 2018)
Acetaminophen (APAP) poisoning is one of the leading causes of acute hepatic failure and liver transplantation is often the only lifesaving alternative. During the course of hepatocyte necrosis, an intense accumulation of neutrophils is often observed within the liver microenvironment. Despite the classic idea that neutrophil accumulation in tissues causes collateral tissue damage, there is a growing body of evidence showing that neutrophils can also orchestrate the resolution of inflammation. In this work, drug-induced liver injury was induced by oral administration of APAP and pharmacological intervention was made 12 h after this challenge. Liver injury and repair kinetics were evaluated by a novel combination of enzyme quantifications, ELISA, specific antagonists of neutrophil enzymes and confocal intravital microscopy. We have demonstrated that neutrophil infiltration is not only involved in injury amplification, but also in liver tissue repair after APAP-induced liver injury. In fact, while neutrophil depletion led to reduced hepatic necrosis during APAP poisoning, injury recovery was also delayed in neutropenic mice. The mechanisms underlying the neutrophil reparative role involved rapid degranulation and matrix metalloproteinases (MMPs) activity. Our data highlights the crucial role of neutrophils, in particular for MMPs, in the resolution phase of APAP-induced inflammatory response.
Keywords: Neutrophil; Matrix metalloproteinases; Liver injury; Sterile inflammation